Effect Of Cobalt’s Chloride On The Optical Properties Of Poly (O-Toluidine) And Study Of It’s Organic/Inorganic Solar Cell - Alfahed, R. K.; Ajeel, K. I.; Hassan, A. K. (European Scientific Journal, ESJ, 2016)
Preparation of poly (o-toluidine) was doped by different volume ratios of cobalt chloride and characterized by (FT-IR, XRD and SEM). The results showed that the intensity of absorption increased while energy gaps of the prepared polymer decreased with respect to increasing ratio of the dopant where the direct and indirect energy gaps were calculated, in addition to edge of the absorption. Photovoltaic device was fabricated by deposit the prepared polymer on the n-type silicon by spin coating method, so the batter efficiency of the prepared devices was 3.02% which was tested under dark and illumination with intensity of 100mW/cm².